2020
DOI: 10.1111/jvh.13222
|View full text |Cite
|
Sign up to set email alerts
|

An observational study on long‐term renal outcome in patients with chronic hepatitis B treated with tenofovir disoproxil fumarate

Abstract: In patients with chronic hepatitis B (CHB), long‐term effects of tenofovir disoproxil fumarate (TDF) on renal function have been controversial. This study aimed to analyse the real‐world long‐term effects of TDF on renal function in Korean patients with CHB. We analysed a cohort of 640 treatment‐naïve patients with CHB who were treated with TDF between May 2012 and December 2015 at Severance Hospital, Seoul, Republic of Korea. The mean age was 48.3 years old, and 59.5% were male. The proportions of hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…In an observatory study of 640 CHB patients who received TDF treatment, the proportion of patients who had decreased renal function greater than 20% and greater than 50% from baseline during the 5-year follow-up was 15.2% and 0.7%, respectively. 21 Another prospective study of 400 CHB patients who received entecavir or TDF for 3 years showed a decrease in the mean eGFR in both groups (P > .05). The proportion of patients with decreased renal function greater than 20% in the TDF group after 3 years of treatment was 16.8%, and that rate was not significantly different than the rate in the entecavir group.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In an observatory study of 640 CHB patients who received TDF treatment, the proportion of patients who had decreased renal function greater than 20% and greater than 50% from baseline during the 5-year follow-up was 15.2% and 0.7%, respectively. 21 Another prospective study of 400 CHB patients who received entecavir or TDF for 3 years showed a decrease in the mean eGFR in both groups (P > .05). The proportion of patients with decreased renal function greater than 20% in the TDF group after 3 years of treatment was 16.8%, and that rate was not significantly different than the rate in the entecavir group.…”
Section: Discussionmentioning
confidence: 95%
“…TmP/GFR was lower in the aggressive dose reduction group than in the standard dose reduction group at every time point, as shown in Figure 3. Percentages of patients with TmP/GFR below 2.4 mg/dL for standard dose reduction group were 17.4%, 30.4%, 21.7%, 21.7% and 26.1% at baseline, month 3, month 6, month 9 and month 12, respectively, whereas percentages of patients with TmP/ GFR below 2.4 mg/dL for aggressive dose reduction group were 39.1%, 47.8%, 43.5%, 47.8% and 43.5% at baseline, month 3, month 6, month 9 and month 12, respectively. However, these differences were not statistically significant.…”
Section: Serum and Urine Parametersmentioning
confidence: 96%
“…As reported previously, renal injury associated with TDF use usually develops after at least one year of treatment. A recent real-world study from Korea showed that TDF therapy did decrease overall renal function in CHB patients during the first two years of TDF use [13]. Therefore, long-term follow-up might be helpful to access the renal impairment in ACLF patients with different antiviral therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, tenofovir (TDF) and entecavir (ETV) are both recommended as the first-line antiviral agents for their potent antiviral activity and high genetic barrier for drug resistance [9,10]. However, TDF has also been demonstrated to have potential kidney toxicity by several observational studies and case reports [11][12][13][14]. It is unclear whether or not the use of TDF may increase the risk of AKI in ACLF.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, concerns about renal toxicity should not limit access to treatment; we found that CHB without treatment also had a risk of CKD progression (consistent with a preceding cohort study (27)), which is not significantly different from the risk in treated patients. Previous studies found that risk factors associated with renal function decline in CHB patients include old age, hypertension, diabetes, baseline eGFR, and use of diuretics (44)(45)(46)(47). Therefore, concerns about nephrotoxicity may be more pertinent in these subgroups, and risks should be assessed on a case-by-case basis.…”
Section: Values Added Into the Existing Literature And Clinical Implimentioning
confidence: 99%